Economic and Environmental Benefits from International Cooperation on Climate Policies - Chateau, Jean.; Jaumotte, Florence; Schwerhoff, Gregor (Washington, D.C. : International Monetary Fund, 2022)
This paper discusses and analyzes various international mechanisms to scale up global action on climate mitigation and address the policy gap in this area. Despite the new commitments made at COP 26, there is still an ambition and a policy gap at the global level to keep temperature increases below the 2 degree C agreed in Paris. Avoiding the worst outcomes of climate change requires an urgent scaling up of climate policies. Recent policy proposals include the idea of common minimum carbon prices, which underlie the IMF's international carbon price proposal (Parry, Black, and Roaf 2021) and the climate club proposal of the German government. While global carbon prices are not a new idea, the new elements are the use of carbon price floors-which allow countries to do more if they wish-and the differentiation of carbon price floors by level of development. In the absence of international coordination, countries with ambitious climate policies are considering introducing a border carbon adjustment mechanism to prevent domestic producers from being at a competitive disadvantage due to more ambitious domestic climate policies. An interesting question from the global perspective is whether border carbon adjustment would deliver substantial additional emissions reductions or incentivize other countries to join a carbon price floor agreement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Allocative Efficiency; Computable and Other Applied General Equilibrium Models; Cost-Benefit Analysis; Trade and Environment